2022
DOI: 10.3390/ijms23073557
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin in Retinal Diseases: A Comprehensive Review from Bench to Bedside

Abstract: Recent evidence in basic science is leading to a growing interest in the possible role of curcumin in treating retinal diseases. Curcumin has been demonstrated to be able to modulate gene transcription and reduce ganglion cell apoptosis, downgrade VEGF, modulate glucose levels and decrease vascular dysfunction. So far, the use of curcumin has been limited by poor bioavailability; to overcome this issue, different types of carriers have been used. Multiple recent studies disclosed the efficacy of using curcumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…In DR model systems, curcumin treatment resulted in an increase in antioxidant enzymes, upregulation of HO-1 and nrf2, reduction or inhibition of inflammatory mediators and growth factors, and inhibition of proliferation and migration of retinal endothelial cells, as evaluated in the different cell lines HRPC, HREC, and ARPE-19. In AMD experimental model systems, curcumin treatment resulted in the reduction of ROS, inhibition of apoptosis mediators and cellular inflammatory genes, and upregulation of the protective enzymes HO-1, thioredoxin, and NQO1 [ 186 , 187 ]. Clinical reports also corroborate the use and efficacy of curcumin in the treatment of ophthalmic pathologies [ 188 ].…”
Section: Nutraceuticals: Which Place In the Management Of Neovascular...mentioning
confidence: 99%
See 1 more Smart Citation
“…In DR model systems, curcumin treatment resulted in an increase in antioxidant enzymes, upregulation of HO-1 and nrf2, reduction or inhibition of inflammatory mediators and growth factors, and inhibition of proliferation and migration of retinal endothelial cells, as evaluated in the different cell lines HRPC, HREC, and ARPE-19. In AMD experimental model systems, curcumin treatment resulted in the reduction of ROS, inhibition of apoptosis mediators and cellular inflammatory genes, and upregulation of the protective enzymes HO-1, thioredoxin, and NQO1 [ 186 , 187 ]. Clinical reports also corroborate the use and efficacy of curcumin in the treatment of ophthalmic pathologies [ 188 ].…”
Section: Nutraceuticals: Which Place In the Management Of Neovascular...mentioning
confidence: 99%
“…[ 202 , 203 ]. The efficacy of curcumin in proliferative retinal diseases has been thoroughly studied and reported [ 187 ].…”
Section: Nutraceuticals: Which Place In the Management Of Neovascular...mentioning
confidence: 99%
“…Early evidence has shown that using curcumin as a therapeutic agent can help to improve the condition of patients with retinal diseases [ 139 , 140 , 141 , 142 ]. Many of these effects have been demonstrated using RPE cells and the retina of diabetic rats as models.…”
Section: Dietary Polyphenols: a Potential Strategy For Management Of ...mentioning
confidence: 99%
“…Curcumin has preventive and therapeutic effects in diabetes, cancer, arthritis, anxiety, allergies, asthma, and many other diseases [ 8 ]. Recent studies have found that curcumin has great potential in the treatment of ocular diseases such as diabetic retinopathy, glaucoma, dry eye and age-related macular degeneration, which can alleviate the inflammatory response due to hyperglycemia and pathological neovascularization in DR [ 9 , 10 ]. It has been found that curcumin can modulate lysosomal activity in several tissues of diabetic rats and exert a lowering effect on blood glucose and urine glucose [ 11 ].…”
Section: Introductionmentioning
confidence: 99%